Digital Transformation: Opening Up Economic Opportunities in The Digital Era - Saladin, Tomy; Faoziyah, Sitti (IJBLE Scientific Publications Community Inc., 2024)
Digital transformation has become a key driver of economic change in the digital era, opening up new opportunities for growth and empowerment of communities. Leveraging technologies such as artificial intelligence (AI), the Internet of Things (IoT), big data, and cloud -based platforms , this transformation enables broader access to global markets, increases business efficiency, and creates new economic models. This article discusses how digital technologies support community empowerment, particularly through the development of MSMEs, financial inclusiveness, and providing access to technology-based education. Digital platforms such as e-commerce and fintech play a critical role in empowering communities previously isolated from the formal economic system. In addition, this transformation also drives innovation in traditional sectors such as agriculture and fisheries through smart technology. However, the adoption of digital transformation faces significant challenges, including gaps in internet access, low digital literacy, and resistance to change. Therefore, collaboration between the government, private sector, and communities is important to ensure inclusivity in the implementation of this technology. Through an integrated approach, digital transformation can not only increase economic competitiveness, but also create a more empowered and equitable society amidst the challenges of the digital era. This article provides an in-depth look at the opportunities, challenges, and strategies to maximize the positive impact of digital transformation on the people's economy.